Company accounting - Jubb, Peter; Haswell, Stephen; Langfield-Smith, Ian. (South Melbourne : Nelson, 1999)
THis book is divided into seven parts: An overview of companies and their regulation, and the financial reporting implications; Accounting for issue of securities; Recognition and measurement of financial statement elements; Reporting and disclosure; External administration; Consolidated accounts; Associates and Joint ventures.
Keywords: Accounting; Economics; Corporations; Corporations -- Australia -- Accounting; Corporations -- Australia -- Accounting -- Problems, exercises, etc; Corporations -- Accounting -- Law and legislation -- Australia